2014
DOI: 10.1039/c4ra04250f
|View full text |Cite
|
Sign up to set email alerts
|

Reusable bacteria immobilized electrospun nanofibrous webs for decolorization of methylene blue dye in wastewater treatment

Abstract: In our study, an electrospun cellulose acetate nanofibrous web (CA-NFW) was found to be quite effective in immobilizing bacterial cells. Here, decolorization of methylene blue (MB) dye in aqueous medium was achieved by using three types of bacteria (Aeromonas eucrenophila, Clavibacter michiganensis and Pseudomonas aeruginosa) immobilized on the CA-NFW. The decolorization time (0-48 h) and different MB dye concentrations (20-500 mg L À1 ) were studied to elucidate the maximum MB dye removal by the bacteria immo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(42 citation statements)
references
References 57 publications
0
41
0
Order By: Relevance
“…11 In recent studies performed by our group, specic bacterial or algal strains have been attached on electrospun brous webs for ammonium bioremoval, 20 methylene blue dye biodegradation, 21 reactive dye biodegradation 22 and simultaneous removal of hexavalent chromium and a reactive dye. 23 In the present study, we focused on anionic surfactant bioremediation and therefore produced novel biocomposite webs by immobilization of two different SDS degrading bacterial strains on electrospun nCA and pCA webs.…”
Section: Reusability and Applicability Of Stb3/pca And Stb4/ Pca Biocmentioning
confidence: 99%
See 1 more Smart Citation
“…11 In recent studies performed by our group, specic bacterial or algal strains have been attached on electrospun brous webs for ammonium bioremoval, 20 methylene blue dye biodegradation, 21 reactive dye biodegradation 22 and simultaneous removal of hexavalent chromium and a reactive dye. 23 In the present study, we focused on anionic surfactant bioremediation and therefore produced novel biocomposite webs by immobilization of two different SDS degrading bacterial strains on electrospun nCA and pCA webs.…”
Section: Reusability and Applicability Of Stb3/pca And Stb4/ Pca Biocmentioning
confidence: 99%
“…11,[20][21][22][23][24] In the current study, Serratia proteamaculans STB3 and Achromobacter xylosoxidans STB4 cells, which have biodegradation capabilities on a known anionic surfactant: sodium dodecyl sulfate (SDS), were immobilized onto cellulose acetate nanobers that have either non-porous or porous morphology to obtain reusable materials for surfactant remediation in aqueous systems. We describe here the development procedure of bacteria immobilized biocomposites and their potential reusability.…”
mentioning
confidence: 99%
“…To overcome this problem, immobilization of microorganisms has been proposed and investigated as a viable means to achieve decolorization and degradation of dyes. 17 For instance, utilization of immobilized Chlorella vulgaris and Scenedesmus rubescens on a membrane system to remove nitrate from municipal wastewater was found to be efficient. 18 In addition, Wang et al 19 showed that employing immobilized Scenedesmus in calcium alginate as algal sheets is efficient in removal of ammonia nitrogen and orthophosphate from municipal wastewater.…”
Section: ■ Introductionmentioning
confidence: 99%
“…36 In another recent study of ours, three different types of bacteria were immobilized on CA-NFW for removal of methylene blue dye. 17 There are studies in the literature related to incorporation of microalgae in electrospun nanofibers. 38−40 For instance, a study by Kim et al 38 fabricated electrospun polycaprolactone nanofiber containing Spirulina and tested as a potential matrix for a culture of primary astrocytes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This lifestyle offers bacteria higher protection from external stresses and thus can lead to problems of eradicating unwanted biofilms. While some bacterial biofilms can be useful for waste water treatment [126,127], starch hydrolysis [128], microbial fuel cells [5,129] and antifouling coatings [130,131] others are harmful, fouling films or pathogens causing hard to treat infections [132].…”
Section: Can the Plasma Treatment Control The Biofilm Formation?mentioning
confidence: 99%